Adenoid cystic carcinoma of base of tongue. (28th June 2012) - Akhavan, Ali; Navabii, Hossein; Saeb, Mohsen
Abstract : Adenoid cystic carcinoma (ACC) is a rare malignant tumour arising from salivary glands. ACC of the head and neck shows a long natural course, high recurrence rates, late metastasis and a tendency for perineural invasion. The authors present a woman with ACC at base of tongue with good response to radiotherapy.